LIVING UNRELATED DONOR KIDNEY-TRANSPLANTATION BETWEEN SPOUSES - HABERAL, M; GULAY, H; TOKYAY, R; ONER, Z; ENUNLU, T; BILGIN, N (SPRINGER VERLAG, 1992)
From November 3, 1975 to November 3, 1990, 874 kidney transplants were performed at our centers. Of these, 675 (77.2%) were from living donors and 199 (22.8%) were from cadaver donors. Five hundred eighty (66.4%) of the living donors were first degree related while 99 (11.3%) were unrelated or second degree related donors, 29 of which were spouses. All donor recipient pairs were ABO-compatible, with the exception of one pair. Donor recipient relations were wife to husband in 25 cases and husband to wife in 4 cases. All were first grafts and started functioning during surgery. In this series, the follow-up for the recipients was 4 to 64 months (mean 33.5 +/- 4.5 months). One-year patient survival and graft survival rates were 92.4% and 81.9%, respectively. Two-year patient survival and graft survival rates were 92.4% and 78.2%, respectively. The single ABO-incompatible case is also doing well, 21 months postoperatively. This study demonstrates that the interspouse kidney transplantation may be used when cadaver organ shortage is a problem. While providing the couple with a better quality of life, interspouse kidney transplantation also enables the couple to share the joy of giving and receiving the gift of life from one another.
Keywords: RENAL-TRANSPLANTATION; TRANSFUSION; Surgery